Characterization of Endophytic Fungi, Acremonium sp., from Lilium davidii and Analysis of Its Antifungal and Plant Growth-Promoting Effects. (4th August 2021) - Khan, Mohammad Sayyar; Gao, Junlian; Munir, Iqbal; Zhang, Mingfang; Liu, Yixin; Moe, The Su; Xue, Jing; Zhang, Xiuhai
Abstract : The present study was aimed at isolating endophytic fungi from the Asian culinary and medicinal plant Lilium davidii and analyzing its antifungal and plant growth-promoting effects. In this study, the fungal endophyte Acremonium sp. Ld-03 was isolated from the bulbs of L. davidii and identified through morphological and molecular analysis. The molecular and morphological analysis confirmed the endophytic fungal strain as Acremonium sp. Ld-03. Antifungal effects of Ld-03 were observed against Fusarium oxysporum, Botrytis cinerea, Botryosphaeria dothidea, and Fusarium fujikuroi . The highest growth inhibition, i.e., 78.39 ± 4.21 %, was observed for B. dothidea followed by 56.68 ± 4.38 %, 43.62 ± 3.81 %, and 20.12 ± 2.45 % for B. cinerea, F. fujikuroi, and F. oxysporum, respectively. Analysis of the ethyl acetate fraction through UHPLC-LTQ-IT-MS/MS revealed putative secondary metabolites which included xanthurenic acid, valyl aspartic acid, gancidin W, peptides, and cyclic dipeptides such as valylarginine, cyclo-[L-(4-hydroxy-Pro)-L-leu], cyclo(Pro-Phe), and (3S, 6S)-3-benzyl-6-(4-hydroxybenzyl)piperazine-2, 5-dione. Other metabolites included (S)-3-(4-hydroxyphenyl)-2-((S)-pyrrolidine-2-carboxamido)propanoic acid, dibutyl phthalate (DBP), 9-octadecenamide, D-erythro-C18-Sphingosine, N-palmitoyl sphinganine, and hydroxypalmitoyl sphinganine. The strain Ld-03 showed indole acetic acid (IAA) production with or without the application of exogenous tryptophan. The IAA ranged from 53.12 ± 3.20 μ g ml -1 to 167.71 ± 7.12 μ g ml -1 under different tryptophan concentrations. The strain was able to produce siderophore, and its production was significantly decreased with increasing Fe(III) citrate concentrations in the medium. The endophytic fungal strain also showed production of organic acids and phosphate solubilization activity. Plant growth-promoting effects of the strain were evaluated on in vitro seedling growth of Allium tuberosum . Application of 40% culture dilution resulted in a significant increase in root and shoot length, i.e., 24.03 ± 2.71 mm and 37.27 ± 1.86 mm, respectively, compared to nontreated control plants. The fungal endophyte Ld-03 demonstrated the potential of conferring disease resistance and plant growth promotion. Therefore, we conclude that the isolated Acremonium sp. Ld-03 should be further investigated before utilization as a biocontrol agent and plant growth stimulator.